2019
DOI: 10.20344/amp.10942
|View full text |Cite
|
Sign up to set email alerts
|

Digital Asthenopia: Portuguese Group of Ergophthalmology Survey

Abstract: Introduction: Given the increasing use of electronic devices, and the increasing number of complaints with its use, we intend to evaluate the prevalence of manifestations of dry eye and ocular fatigue in a population of individuals, who use the computer daily to perform all their professional tasks, as well as to correlate these complaints with the number of hours of digital use as well as their possible improvement with behavioural measures and use of tear drops.Material and Methods: A total of 77 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 5 publications
(5 reference statements)
0
48
0
5
Order By: Relevance
“…The other one is the management of binocular dysfunction as it is possible to improve accommodation demand by looking down and in simultaneously [21,26] Treating dry eye is also the other known method to prevent CVS [17,50,51]. Triphala eye drops are known to reduce as well as to increase visual function as indicated by Gangamma M, et al [27].…”
Section: Prevention and Treatment Of Cvsmentioning
confidence: 99%
“…The other one is the management of binocular dysfunction as it is possible to improve accommodation demand by looking down and in simultaneously [21,26] Treating dry eye is also the other known method to prevent CVS [17,50,51]. Triphala eye drops are known to reduce as well as to increase visual function as indicated by Gangamma M, et al [27].…”
Section: Prevention and Treatment Of Cvsmentioning
confidence: 99%
“…Previous studies have reported that individuals interact with digital screens for up to 12 hours daily [1,2], and the American Optometric Association defined a combination of ocular and extraocular symptoms that affects the screen users as computer vision syndrome (CVS) [3]. However, our current understanding of digital technologies and their harmful impact on the eye and public health [1,4,5], visual performance [6][7][8], sleep patterns [7,8], circadian rhythms [5,8], musculoskeletal system activities [3,4], and underlying physiological mechanisms [9] remains incomplete and replete with misconceptions [1]. erefore, educational programs that include protective measures and health campaigns are necessary [10].…”
Section: Introductionmentioning
confidence: 99%
“…Computer vision syndrome (CVS) is also called by other names as digital eye strain (DES) [3], occupational asthenopia [11], digital asthenopia [1], and video display terminal syndrome (VDTS) [12,13]. CVS ocular symptoms include visual blur with an underlying mechanism that is not fully understood [10], dry eye disease (DED) [3,14,15], eye redness and irritation, eyestrain, fatigue, discomfort [14,16], difficulty in refocusing the eyes, and diplopia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in other developed countries have shown an increase in asthenopia among adolescents, which is shown to be related to their e-device usage. 57,58 All the above-mentioned studies noted a significant prevalence of CI among school-going children. Recent evidence shows that CI has been associated with the intense visual demand required of schooling children, 44 with Wajuihian et al 48 also noting that near work adversely affects the visual system.…”
Section: Convergence Insufficiency In School-going Childrenmentioning
confidence: 98%